EFEKTIVITAS DISEMINASI INFORMASI MEDIA SOSIAL INSTAGRAM PPID DPR RI - Fajran Akhdan; Saifullah Zakaria; Jovanscha Qisthy Adinda (LPPM Universitas Abdurrab, 2026)
media as a channel for public information dissemination, including PPID of the House of Representatives of the Republic of Indonesia through Instagram. This study aims to analyze the effectiveness of public information dissemination through the PPID DPR RI Instagram account in supporting public information disclosure. The research employs a qualitative descriptive method using observation, interviews, and documentation. Data are analyzed using the public communication effectiveness framework of Barcelona Principles 3.0. The findings indicate that information dissemination through the PPID DPR RI Instagram account has been implemented consistently and functions as an educational medium and an initial gateway to public information access. However, its effectiveness has not been fully optimized, as performance measurement remains focused on technical social media metrics and has not adequately captured communication outcomes. Practically, this study highlights the need to strengthen integrated digital communication performance indicators oriented toward public understanding and information-seeking behavior, in order to support public information disclosure more strategically.